Pola Komunikasi Komunitas Kaskus Regional Riau Raya dalam Membentuk Kohesivitas Kelompok - Tika Wulandari; Nova Yohana, (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
The entry and development of the internet has increased the number ofoccurrences of cybercommunities, one of them is Kaskus Regional Riau RayaCommunity. Kaskus Regional Riau Raya do the interaction and communication toimprove the existence, solidarity among members, and cohesiveness within thegroup. The aim of this research are to determine the communication pattern ofvirtual communication (online communication), and the communication pattern offace to face communication (offline communication) among Regional Riau Raya’skaskusers in forming their group cohesiveness.This research used descriptive qualitative approach, with the selection ofinformants using purposive sampling technique, which selects five informants,which is a Regional Leader, two Regional Activist, and two regular kaskuser. Thedata collection techniques are used observation, in-depth interviews, anddocumentation. While, for the data analysis was refer to the interactive model ofHuberman and Miles. Then, for checking the validity of data were usingtriangulation and extension participation techniques.From this research concluded that virtual communication is realized in avariety of online activities with various motivations, such as for pursuit of theirstatus, sharing informations and stories, planning, complaints, and also buyingand selling activities. While face to face communication is realized in a variety offormal events, informal events, meetings with the aim of completing the tasks, orjust to share some stories. Both the virtual and face to face communication isimplemented in Two-Way Communication, and with All Channels CommunicationPattern. These communication pattern formed the group cohesiveness that makesRegional Riau Raya’s kaskuser maintain each other.Keywords: Kaskus Regional Riau Raya Community, virtual communicationpattern, face to face communication pattern, cohesiveness